2021
DOI: 10.3847/2041-8213/abdaaf
|View full text |Cite
|
Sign up to set email alerts
|

The Ion Transition Range of Solar Wind Turbulence in the Inner Heliosphere: Parker Solar Probe Observations

Abstract: The scaling of the turbulent spectra provides a key measurement that allows us to discriminate between different theoretical predictions of turbulence. In the solar wind, this has driven a large number of studies dedicated to this issue using in situ data from various orbiting spacecraft. While a semblance of consensus exists regarding the scaling in the magnetohydrodynamic (MHD) and dispersive ranges, the precise scaling in the transition range and the actual physical mechanisms that control it remain open qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 86 publications
3
26
0
Order By: Relevance
“…Furthermore, other parameters of the plasma, such as plasma beta [48], ion-to-electron heating rate [49,50] and/or effects of outer scale separation [51] may influence the properties of sub-ion scale cascade. Recent PSP observations [24,26] of a young solar wind suggest that the level normalized cross-helicity (imbalance between the counter-propagating Alfvén wave packets) may play a role in the dynamics of the transitional range, which may lead to the observed steepening. Huang et al [26] reported a weak anticorrelation between the transition range spectral index and cross-helicity, in relative terms, such a trend is qualitatively consistent with Figure 8 because higher levels of inertial range fluctuations are characteristic for fast solar wind [52], which exhibits non-zero cross-helicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, other parameters of the plasma, such as plasma beta [48], ion-to-electron heating rate [49,50] and/or effects of outer scale separation [51] may influence the properties of sub-ion scale cascade. Recent PSP observations [24,26] of a young solar wind suggest that the level normalized cross-helicity (imbalance between the counter-propagating Alfvén wave packets) may play a role in the dynamics of the transitional range, which may lead to the observed steepening. Huang et al [26] reported a weak anticorrelation between the transition range spectral index and cross-helicity, in relative terms, such a trend is qualitatively consistent with Figure 8 because higher levels of inertial range fluctuations are characteristic for fast solar wind [52], which exhibits non-zero cross-helicity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent PSP observations [24,26] of a young solar wind suggest that the level normalized cross-helicity (imbalance between the counter-propagating Alfvén wave packets) may play a role in the dynamics of the transitional range, which may lead to the observed steepening. Huang et al [26] reported a weak anticorrelation between the transition range spectral index and cross-helicity, in relative terms, such a trend is qualitatively consistent with Figure 8 because higher levels of inertial range fluctuations are characteristic for fast solar wind [52], which exhibits non-zero cross-helicity. We plan to address the role of cross-helicity in a future study that will employ hybrid-kinetic simulations and the technique introduced in the current manuscript.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been devoted to the investigation of spectral breaks at both low and high frequencies (e.g., Markovskii et al 2008;Bruno et al 2014Bruno et al , 2017, as well as, to link the location of these breaks to spatial scales in the plasma frame (e.g., Bourouaine et al 2012), mostly related to both ion gyroradius and inertial length (Chen et al 2014). However, various physical processes operate near the observed spectral break (around 1 Hz) such that a direct connection with a peculiar dynamics (e.g., waves vs. instabilities, dispersion vs. damping mechanisms) is really difficult at 1 AU solar distance, thus still remaining an open question (e.g., Alexandrova et al 2013;Huang et al 2021). By searching for scaling-law behaviors and looking at high-order statistics several insights have been provided on turbulence and intermittency (Kolmogorov 1941(Kolmogorov , 1962 as well as on both the direct and inverse energy/enstrophy cascade mechanisms (Matthaeus & Goldstein 1982;Sorriso-Valvo et al 2007).…”
mentioning
confidence: 99%